Effectiveness of the Mini-Mult in detecting MMPI pathology in the blind - Needham, Walter E.; Ehmer, Marjy N.; Marchesseault, Linda; l'Aune, William R. De (Journal of Clinical Psychology, 1986)
The Mini‐Mult and MMPI were administered in random order to 60 blind male veterans admitted to a residential rehabilitation program. Mini‐Mult scores predicted the presence or absence of MMPI pathology in 81.7% of the cases. Correlations between the individual Mini‐Mult and MMPI scales were significant at the p < .01 level, but not of sufficient magnitude to permit their interchangeability or to allow for profile diagnosis on the basis of Mini‐Mult scores. Analysis of the false negatives raises questions about the clinical significance of an abnormal MMPI in the population studied. The results support the value of the Mini‐Mult as a screening device, but not as a substitute for a detailed psychological assessment of the blind. Copyright © 1986 Wiley Periodicals, Inc., A Wiley Company
Keywords: Blindness; Human; MMPI; Male; Mass Screening; Mental Disorders; Middle Age; adult; blindness; central nervous system; clinical article; dept.psy; human; priority journal; psychological aspect; rehabilitation; visual system

Premorbid social competence and psychiatric outcome in male and female nonschizophrenic patients - Glick, Marion; Zigler, Edward (Journal of Consulting and Clinical Psychology, 1986)
The relation between premorbid social competence and outcome was examined in 448 (228 male and 220 female) first-admission, nonschizophrenic, state-hospital patients. For both sexes, higher social competence was related to more favorable outcome as reflected in shorter initial hospitalizations and shorter rehospitalizations. Consistent with a developmental formulation, these results provide further evidence that the relation between premorbid competence and outcome is not unique to schizophrenia but can be found for patients of both sexes across a range of diagnoses. © 1986 American Psychological Association.
Keywords: adult; central nervous system; clinical article; competence; dept.psy; human; mental patient; psychological aspect; social aspect; social behavior; therapy

Young-children reinvent arithmetic - implications of piaget theory - kamii,ck, declark,g - Smith, JP (Teachers College Record, 1986)
Keywords: dept.psy; ⛔ No DOI found